Outcomes from a pilot psychological therapies service for UK military veterans. Issue 4 (28th June 2016) - Clarkson, Paul; Giebel, Clarissa M.; Challis, David; Duthie, Paul; Barrett, Alan; Lambert, Helen
Abstract: Aim: To evaluate the outcomes of participants attending a psychological therapies service for military veterans. Background: The UK Military Veterans' Improving Access to Psychological Therapies Service (North West) (MV IAPT) provided a clinical psychological therapies service for military veterans. Outcomes of depression, anxiety and social adjustment were assessed after treatment in the service's pilot phase. Design: An observational, prospective cohort study examined changes in depression, anxiety and social adjustment during receipt of the service. Methods: Changes in depression (PHQ‐9), anxiety (GAD‐7) and social adjustment (WSAS) were examined in 952 veterans referred over 20 months from September 2011. Data were collected using the IAPT clinical information system plus additional fields. Changes for patients who completed treatment, remained in treatment and dropped out were compared. Results: Seven hundred and seven veterans received an initial assessment, from which 505 received two or more appointments. Of these, 156 completed treatments, 179 remained in treatment and 170 dropped out. The majority of veterans had been operationally deployed and were similar in risk characteristics to those in other military cohort studies. There were highly significant improvements on all measures ( p <.01), with completers improving more and having higher rates of recovery from depression and anxiety than those remaining and drop outs. Recovery rates compared favourably with evaluations of general IAPT services and also exceeded reported natural recovery rates.